Sports justice : the law & the business of sports - Abrams, Roger I., 1945- (Boston, Mass. : Northeastern University Press ; Hanover, N.H. : Published by University Press of New England, 2010)
In this accessible and fascinating look at law and sports, Roger I. Abrams shines the lights on the uniquely complex and important legal issues that face both amateur and professional athletes. From cases involving Title IX, transgendered athletes, rights of the disabled, violence on the playing field, individual and franchise free-agency, amateurism and college sports, and responsibility of leagues for the safety and lifelong health of injured players, Abrams weaves a profoundly moving and immediately relevant story of ever broadening access to, and expanding rights within, the field of sports. Abrams illuminates these legal cases through compelling storytelling and personal explorations of those involved, such as Jeremy Bloom, the world champion mogul skier who was barred from playing college football because he had modeled clothes for Tommy Hilfiger, and Casey Martin, Renee Richards, and the young gymnasts from Brown University who sought access to the sports they loved, but found that their quest to achieve justice required judicial intervention. There is also one non-athlete: Al Davis, the renegade owner of the Oakland-Los Angeles-Oakland Raiders, who beat the National Football League cartel using the antitrust laws in his effort to gain the respect he was always denied. Written for sports fans and legal scholars alike, this is an engrossing and surprising story of people battling for their careers and lives, and in the process changing the very nature of sports and society.
Stay out of my court -- Swing for the green, if you can : the rights of disabled athletes -- Gender identity in a changing world : tennis anyone? -- The ideal of amateurism : NCAA regulation of the college cartel -- Sports arbitration and enforcing promises -- Gender equity on the parallel bars : Title IX and the changing vision of American sports -- Sticks are swinging, but is it a crime -- Al Davis, Pete Rozelle, and franchise free agency -- The tight end, freedom, and the antitrust laws -- T.O. meets the arbitrator.
Includes bibliographical references (pages 205-207) and index.
Keywords: Sports -- Law and legislation -- United States; Athletes -- Legal status, laws, etc. -- United States; Athletes with disabilities -- Law and legislation -- United States